2022
DOI: 10.1177/00104140211047414
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Rules, Women’s Representation and the Qualification of Politicians

Abstract: Proportional electoral rules are associated with more substantial women’s representation than majoritarian ones. To provide causal evidence that electoral rules affect women’s representation and the qualification of politicians, we collect panel data on the universe of Italian politicians from all levels of government over the period 1987–2013 and analyse an Italian reform which, in 2005, changed the electoral rule for national elections from (mostly) majoritarian to proportional, but did not affect subnationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Out of 286 respondents, 5 respondents gave their views except for these given options. The examination of Italy's governmental levels from 1987 to 2013 has also demonstrated that proportional electoral systems are linked to a greater degree of female representation compared to majoritarian systems (Profeta & Woodhouse, 2022). They wrote that it depends on the women candidates and how they perform in the election fray.…”
Section: Appropriate Electoral System For Female Candidatesmentioning
confidence: 99%
“…Out of 286 respondents, 5 respondents gave their views except for these given options. The examination of Italy's governmental levels from 1987 to 2013 has also demonstrated that proportional electoral systems are linked to a greater degree of female representation compared to majoritarian systems (Profeta & Woodhouse, 2022). They wrote that it depends on the women candidates and how they perform in the election fray.…”
Section: Appropriate Electoral System For Female Candidatesmentioning
confidence: 99%
“…Observational research from the US and Europe has shown there is a gender gap in the qualifications men and women possess when running for office. On average, women have higher levels of qualifications, experience, and education than men (Fulton, 2012;Profeta & Woodhouse, 2022). Work on quotas in Italy and Sweden has found quota-women to be more qualified than non-quota men (O'Brien & Rickne, 2016;Weeks & Baldez, 2015).…”
Section: Gender Qualifications and Voter Evaluationsmentioning
confidence: 99%
“…8 For quotas, see Bush (2011), Clayton (2021, and Clayton and Zetterberg (2018). 9 Aldrich (2020), Luechinger, Schelker, and Schmid (2023), Profeta and Woodhouse (2022), Roberts, Seawright, and Cyr (2013), Salmond (2006), Skorge (2023), Thames (2017).…”
Section: Introductionmentioning
confidence: 99%